2015
DOI: 10.1212/wnl.0000000000001307
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric symptoms, APOE ε4, and the risk of incident dementia

Abstract: Objective: To investigate the population-based interaction between a biological variable (APOE e4), neuropsychiatric symptoms, and the risk of incident dementia among subjects with prevalent mild cognitive impairment (MCI). Methods:We prospectively followed 332 participants with prevalent MCI (aged 70 years and older) enrolled in the Mayo Clinic Study of Aging for a median of 3 years. The diagnoses of MCI and dementia were made by an expert consensus panel based on published criteria, after reviewing neurologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
103
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(114 citation statements)
references
References 38 publications
5
103
0
2
Order By: Relevance
“…NPS are common in Mild Cognitive Impairment (MCI), and are associated with poorer cognitive and psychosocial function within MCI cohorts [13, 14]. Population-based [15, 16] as well as clinic-based cohort studies [17] provide consistent evidence that NPS in MCI are associated with higher risk for incident dementia, with an estimated annual rate of progression to dementia of 25% for MCI plus NPS [17] in contrast to the rate for MCI of 10 to 15 % per year [18]. Similarly, NPS in older adults with normal cognition confers a higher likelihood of progression to MCI and dementia, as shown in the Alzheimer’s Disease Cooperative Study [19], one Alzheimer’s Disease Research Center [20], the Danish Psychiatric and Somatic Health Register [21], the Mayo Clinic Study of Aging [22], the Medical Research Council Cognitive Function and Ageing Study [23] and the National Alzheimer’s Coordinating Center database [24, 25].…”
Section: Introductionmentioning
confidence: 99%
“…NPS are common in Mild Cognitive Impairment (MCI), and are associated with poorer cognitive and psychosocial function within MCI cohorts [13, 14]. Population-based [15, 16] as well as clinic-based cohort studies [17] provide consistent evidence that NPS in MCI are associated with higher risk for incident dementia, with an estimated annual rate of progression to dementia of 25% for MCI plus NPS [17] in contrast to the rate for MCI of 10 to 15 % per year [18]. Similarly, NPS in older adults with normal cognition confers a higher likelihood of progression to MCI and dementia, as shown in the Alzheimer’s Disease Cooperative Study [19], one Alzheimer’s Disease Research Center [20], the Danish Psychiatric and Somatic Health Register [21], the Mayo Clinic Study of Aging [22], the Medical Research Council Cognitive Function and Ageing Study [23] and the National Alzheimer’s Coordinating Center database [24, 25].…”
Section: Introductionmentioning
confidence: 99%
“…It is well accepted that the comorbid presentation of NPS in MCI is linked to higher progression to dementia [9][10][11][12][13][14][15] and that for patients with Alzheimer's disease (AD), NPS are associated with an increased likelihood of progression from mild to severe dementia [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have found an association between amyloid deposition with a faster cognitive decline in both cognitively normal elderly (Chetelat et al , 2012; Knopman et al , 2012; Morris et al , 2009; Petersen et al , 2016) and MCI subjects (Jack et al , 2010; Jagust et al , 2010). A growing body of research has shown that depressive and anxiety symptoms may increase the risk of cognitive decline (Geda et al , 2006; Geda et al , 2008; Geda et al , 2014; Pink et al , 2015). Furthermore, we and others have reported that depressive (Donovan et al , 2015; Krell-Roesch et al , 2016) and anxiety symptoms (Pink et al , 2017) are associated with neuroimaging biomarkers of AD, specifically FDG-PET and cortical thickness as measured by MRI, among cognitively normal elderly participants.…”
Section: Introductionmentioning
confidence: 99%